Word and world : practice and the foundations of language - Hanna, Patricia (Cambridge University Press, 2004)
"A provocative reexamination of the interrelations of language and social practice, this book will interest not only philosophers of language but also literary theorists, linguists, psycholinguists, students of communication, and all those concerned with the nature and acquisition of human linguistic capacities."--Jacket